1987
DOI: 10.1016/0278-5846(87)90020-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic properties of desipramine and amoxapine: Assessment using a thermoregulation paradigm

Abstract: 1. The withdrawal of tricyclic antidepressants (TCAs) produces symptoms suggesting cholinergic rebound. 2. Amitriptyline (AMI), the most potent antimuscarinic agent among this class of drugs, produces supersensitivity to the muscarinic agonist, oxotremorine. 3. Enhancement of the sensitivity of cholinoceptive neurons to acetylcholine as a consequence of treatment with TCAs would account for many of the symptoms following the withdrawal of these drugs. 4. Desipramine (DMI) is the least potent antimuscarinic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, the vagal efferent fibers should play a critical role in the dynamic baroreflex control of HR, because the vagal control is much faster than the sympathetic control (4,18). Although desipramine is the least potent antimuscarinic compound among the tricyclic antidepressants (10), it could affect the vagal control of HR via the interaction between the vagal and sympathetic systems (18,23). Further studies are required to elucidate the effects of desipramine on the dynamic vagal control of HR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the vagal efferent fibers should play a critical role in the dynamic baroreflex control of HR, because the vagal control is much faster than the sympathetic control (4,18). Although desipramine is the least potent antimuscarinic compound among the tricyclic antidepressants (10), it could affect the vagal control of HR via the interaction between the vagal and sympathetic systems (18,23). Further studies are required to elucidate the effects of desipramine on the dynamic vagal control of HR.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment with TCAs produces supersensitivity of a central muscarinic mechanism Dilsaver and Davidson, 1987;Dilsaver and Snider, 1988). Hyperfunction of central muscarinic mechanisms may be involved in the biology of depression (Janowsky et al, 1972;Dilsaver, 1986a-6).…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressant withdrawal symptoms respond to centrally active antimuscarinic agents (28,29). Finally, my associates and I have demonstrated that amitriptyline (30,31), amoxapine and desipramine (32) all enhance sensitivity of a central muscarinic mechanism to the hypothermic effects of oxotremorine.…”
Section: Neurobiology Of Antidepressant Withdrawal Symptomsmentioning
confidence: 97%